ISLAM IN THE CHALLENGE OF THE GLOBAL CULTURAL AND MODERN WORLD - Mohamad Hambali Rashid; Dr Shukri Ahmad (Journal of Islamic, Social, Economics and Development, 2018)
Islam is the religion of rahmatan Lil Alamin. It's based on the principle of morality, the unity of the Ummah, peace and progress, Islam is spreading all over the globe to become one of the world's largest religions. The Islamic position that transcends the various races and cultures causes it to be a religion that is full of value, accepting local values to be a part of the way of life as long as it conforms to the creed of Islam. Islam, then has seeped into different forms of culture, but the aspect of unity and obedience becomes the axis of acceptance of every culture. Since the beginning of development, the Islamic community has succeeded in overcoming the world's civilization in various fields of life. However, it gradually develops a deterioration when the principle value is no longer prioritized. The political instability and social challenges that are very serious in the world of Islamic societies cause the Muslims to resign. This paper seeks to explore and analyze the diversity of Islamic-related issues and cultural challenges involving several aspects such as value, modernization, technology and knowledge. Additionally, this paper will also address the expected solutions that can help overcome the challenges of the people towards their revival in the 21st century. The analysis of this paper was carried out by using content analysis based on critics and opinions from Islamic and non-Muslim scholars and intellectuals.